APLIKASI PUPUK ORGANIK CAIR KOTORAN SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERONG GELATIK (Solanum melongena L.) - Farida, Farida; Rohaeni, Nani (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
Research of application organic fertilizer of liquid cow dung on growth and yield of eggplant. The research purpose to recognize fertilizer application of liquid cow dung on growth and yield of eggplant gelatik and know some concentration of liquid organic fertilizer cow dung is best to growth and yield of plant eggplant gelatik. The research was conducted of Desember 2018-March 2019, in Pertamina KM 04 Road North Sangatta East Kutai Regency. The research design used was non factorial rondomized block repeated 5 times. The fertilizer (P) factor consists of 5 levels : P0 = control, P1 = 5 cc/liter of water/plant, P2 = 10 cc/liter of water/plant, P3 = 15 cc/liter of water/plant, P4 = 20 cc/liter of water/plant. The results showed that application of organic fertilizer liquid cow dung very significant to the parameter of plant height and the number of leaves age 30 HST, showed significant to 45 HST and the weight of the harvest. But showed no significant to parameter height and number of leaves age 15 HST and age of flawers 75%. Treatment of P2 showed the best result to parameter of fruti weight is 1,181 gram/plant.Key word : POC, eggplant gelatik, cow dung